Mandat (creadential) dalam budaya mitigasi bencana pada masyarakat Kampung Budaya Sindang Barang (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Mandate (credential) as mitigation culture on local community of Sindang BarangLocal wisdom can be learned through discovery of physical elements of traditional villages, such as spatial layout, architectural objects, and daily activities. The organization prevailing in environment plays an important role in managing a contextual mitigation culture. The co-existence of authority (mandate) masters have the authority of value/cultural capital and to create symbolic elements, such as will or belief. Sindang Barang Cultural Village was taken as a case study to reveal the history and role of the mandate in the culture of disaster mitigation. This study aims to observe the role of the mandate and its impact in disaster mitigation. The role of the mandate is also examined to see the existence of efforts to preserve the values of local wisdom towards the times. This research uses descriptive-qualitative method by tracing the phenomena and artifacts in the field. The analysis carried out in two phases. The first phase is to create a mitigation concept table based on the existing program or artifacts.  The second phase is to discuss the mitigation culture based on its classified capacities. The mitigation seen from the Sindang Barang Cultural Village program and artifacts is the risk of fire, earthquake, and landslide. The process of determining a mandate is commensurate with adaptive capacity because this stage tends to lead to restriction or orders about in program that is carried out systematically in particular context.
Keywords: Adaptive capacity; Culture of mitigation; Local Wisdom; Sindang Barang